A New Metallic Damper for Seismic Resilience: Analytical Feasibility Study. (August 2016) - Basu, Dhiman; Reddy, P.R.M.
Abstract: This paper explores the feasibility of a metallic damper that enables dissipation of input energy regardless of the direction of seismic excitation. Also explored is the feasibility of appropriate mounting system. Feasibility study carried out here is restricted to the analytical domain: A ten-storied building located in a seismically active region of India and three seismic events recorded at the Large Scale Seismic Testing (LSST) array, Lotung, Taiwan. Merits of the proposed damper and its mounting system are evident over the commonly used X-plate systems but the extent of benefits depends on the types of ground motion. Component level testing indicates that necking may not be a serious concern in proposed device.